2020
DOI: 10.3390/pharmacy8010028
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pharmacy Technician Roles in the Implementation of an Appointment-Based Medication Synchronization Program

Abstract: The objective of this study was to qualitatively explore the role of pharmacy technicians in the implementation of an appointment-based model (ABM) medication synchronization program. The purposeful sampling of technicians working within six different locations of a supermarket chain pharmacy in Mississippi and Tennessee was carried out, and the technicians were interviewed between January and April 2018. A semi-structured interview guide was developed based on the Consolidated Framework for Implementation Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…The tasks in which techniciansmight assume greatest responsibility include identifying patients for marketing and enrollment, reviewing patients’ medication lists, choosing alignment dates based on patient preference, contacting patients in preparation for dispensing, and engaging in pickup or delivery of medications. A second study employed the Consolidated Framework for Implementation Research (CFIR) to examine not only initial design, but the sustainability of med sync ABM services [ 6 ]. The study found that among pharmacy technicians engaged in helping coordinate and deliver these services, in an absence of proper planning for workflow and job redesign, that other tasks might sometimes get short shrift; however, they expressed confidence that minor system flaws can be adjudicated and expressed considerable enthusiasm for their role in helping patients.…”
mentioning
confidence: 99%
“…The tasks in which techniciansmight assume greatest responsibility include identifying patients for marketing and enrollment, reviewing patients’ medication lists, choosing alignment dates based on patient preference, contacting patients in preparation for dispensing, and engaging in pickup or delivery of medications. A second study employed the Consolidated Framework for Implementation Research (CFIR) to examine not only initial design, but the sustainability of med sync ABM services [ 6 ]. The study found that among pharmacy technicians engaged in helping coordinate and deliver these services, in an absence of proper planning for workflow and job redesign, that other tasks might sometimes get short shrift; however, they expressed confidence that minor system flaws can be adjudicated and expressed considerable enthusiasm for their role in helping patients.…”
mentioning
confidence: 99%
“…Developing and implementing medication synchronization program can be quite challenging. [37][38][39][40][41]…”
Section: Discussionmentioning
confidence: 99%